Performance and Success of ICT Teams: a Continuous Management Model - Terra, Marcus Vinicius Alencar; Oliveira, Kênia Xavier Teodoro De; Barros, Rodolfo Miranda De (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Human performance management is an essential process within organizations, through which it is possible to improve, among other things, the efficiency, productivity and satisfaction of employees. Its benefits are even more evident in areas such as Information Technology (IT), where complexity and uncertainty are constant factors and professionals must possess a high level of knowledge and creativity. Problem: Post-modern society has transformed performance related issues into situations that are merely focused on goals and competitiveness, which generates, in IT employees, the feeling of being under constant pressure due to the need to deliver immediate results. Solution: This study proposes a performance management model for IT professionals, linked to the Agile and Success Management concepts and addressing aspects such as the continuous feedback and developing, check-in meetings, innovation, value delivery, IT employee engagement and empowerment. IS Theory: This article was developed under the aegis of Success Management Theory, particularly with regard to the concept that success needs to be understood by considering the perspective of all stakeholders and must be continuously potentiated. Method: The research method used was Design Science Research, being prescriptive in nature with a qualitative analysis approach based on established requirements. Summary of Results: The model developed was considered functional and fully adherent to the agile best practices, responding positively to the requirements of continuous performance management, developing and coaching IT teams in order to guarantee the success of a endeavor. Contributions and Impact in the IS area: The main contribution of this study is the proposition of a agile model for human performance management, based on continuous feedback and development of IT teams. This research has a positive impact on IT performance (individual, team and organizational), continually improving the relationship between IT employees and organizations